2021
DOI: 10.1016/j.jseint.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional kinematics of reverse shoulder arthroplasty: a comparison between shoulders with good or poor elevation

Abstract: Background Various factors may be related to outcomes of reverse shoulder arthroplasty (RSA) including patient and surgical factors. Differences in shoulder kinematics might be associated with poor function after RSA; however, kinematic differences between shoulders with good or poor elevation have not been elucidated. The purpose of this study was to compare RSA kinematics between shoulders with good or poor elevation. Methods The study included 28 shoulders with a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…While the transversal body axis can be easily determined clinically, the measurement of the scapular axis is limited, because the center of the glenoid cannot be assessed and therefore the bony landmarks used for CT-measurements cannot be utilized. However, surface-level landmarks can be used as substitutes to assess changes in scapulothoracic orientation and evaluate scapulohumeral rhythm [21,22]. Due to skin shifting during movement invasive procedures like pin insertion into bony landmarks seem to be most accurate but certainly practically not feasible, which is why less-invasive procedures like motion sensors, biplane fluoroscopy and simple goniometer measurements are being considered [6,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…While the transversal body axis can be easily determined clinically, the measurement of the scapular axis is limited, because the center of the glenoid cannot be assessed and therefore the bony landmarks used for CT-measurements cannot be utilized. However, surface-level landmarks can be used as substitutes to assess changes in scapulothoracic orientation and evaluate scapulohumeral rhythm [21,22]. Due to skin shifting during movement invasive procedures like pin insertion into bony landmarks seem to be most accurate but certainly practically not feasible, which is why less-invasive procedures like motion sensors, biplane fluoroscopy and simple goniometer measurements are being considered [6,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional descriptive study involving 90 female participants demonstrated that breast cancer treatment resulted in alterations in the neuromuscular activity of the shoulder. These alterations were associated with the presence or absence of persistent pain and were more pronounced when persistent pain was present [29].…”
Section: Breast Cancer and The Associated Complications Following Bre...mentioning
confidence: 93%